Effect of OPC and PFA cement on stabilised peat bricks - Deboucha, S.; Hashim, Roslan (Academic Journals, 2010)
The paper presents a study of compressive strength, water absorption and apparent porosity of different types of compressed stabilised peat bricks. Peat soil, sand, PFA cement or OPC cement were steam autoclaved under different conditions to produce brick samples. The percentage of peat soil 20, PFA and OPC cement was between 20-30, and sand ranged from 50-60. The effect of each component of the mixtures on compressive strength, water absorption and apparent porosity of compressed stabilised peat after 3, 7, 14 and 28 days of conservation at 23 Â± was 2Â°C. The compressive strength increased with increased binder ration. However, strength of mixture with PFA cement was higher than OPC cement. The water absorption decreased with increased ration of binder and period time. The apparent porosity decreased with increased period time. The compressive strength, water absorption and porosity of cemented peat bricks obtained at 28 days for both stabilisers PFA and OPC cement were 6.33 and 5.91 Mpa, 2.6 and 5.4 and 4.75 and 9.7, respectively. The results demonstrate that the cemented peat bricks can be used as construction building material.